Cytokine Gene Polymorphism in Children With Idiopathic Nephrotic Syndrome (Iranian Journal of Kidney Diseases, 2017)
Introduction. Idiopathic nephrotic syndrome (INS) is a glomerular disease with completely unclear pathogenesis and different responses to steroid therapy. This study aimed to investigate the role of cytokine genes promoter polymorphisms in steroid therapy responses. Materials and Methods. One hundred children with INS and 30 healthy controls were studied. Genotyping of TNF-α-G308A single nucleotide polymorphism was done using polymerase chain reaction-restriction fragment length polymorphism method, while of IL-6-G174C single nucleotide polymorphism was done using real-time polymerase chain reaction. Results. The IL-6-G174C exhibited a significantly different genotype distribution among the children with INS compared with the controls (GG versus CC, P = .02; GG versus GC, P = .003; odds ratio [OR], 5.83; 95% confidence interval [CI], 1.64 to 20.70; as well as alleles distribution of G versus C, P ? .001; OR, 7.57; 95% CI, 2.28 to 25.17). With regard to TNF-α-G308A genotype, there was no significant difference in genotype distribution of the children with INS compared with the controls, but a significant difference was observed at the alleles level. Comparing the steroid-resistant group with the steroid-sensitive group, significant association was found at genotypic level in case of IL-6-G174C (GG versus CC, P = .03; OR, 5.52; 95% CI, 1.39 to 21.89), but no association was found regarding GG versus GC. At the allelic level of IL-6-G174C, there was no significant association either. Conclusions. IL-6-G174C and TNFα-G308A polymorphisms may affect susceptibility to idiopathic nephrotic syndrome and might affect steroid response in INS patients.